The personal, psychological, social and economic experiences of single mothers - Catapang, Anne Marie P. (Animo Repository, 1997)
The purpose of this study is to identify and describe the personal, psychological, social and economic experiences of the unwed, separated, temporary and widows as single parents. This study utilized a descriptive and comparative research design to gather the necessary data. The sample consists of twenty (20) single mothers who were obtained through Chain-referral and Convenience sampling. Four (4) of them are unwed, six (6) of them are separated, (6) of them are temporary single and four (4) of them are widows. All the participants are currently residing in Metro Manila. The in-depth interview method with the aid of a structured interview guide composed of open-ended questions was utilized in acquiring the needed information. In analyzing the data, Cross-category analysis was done. Their responses were first categorized then described and compared. Findings indicated that most of the unwed participants reason for not marrying was unfinished studies and financial instability. For most of the separated, unfaithfulness of husbands was their reason. For the temporary single, professional fulfillment and financial problems were the basic reasons why their husbands work abroad. For most of the widow participants, illness have been the cause of their partners' death. It was found that most of the single mother participants encounter similar problems but vary on the degree to which they experience it. In order to overcome these problems, most of them resorted to prayers as their coping mechanism. It was also discovered that only most of the unwed and temporary single mothers have experienced a change in their priorities from the time they were not yet single mothers and now that they are, while most of the separated and widow participants have maintained their families as their highest priority. Being independent was the learning gained by most of the participants in the process of raising their children alone. Findings revealed that feeling bad/sad for their children had been felt by single mother participants and